The Effect of Career Development and Motivation of Employee Performance in Syariah Mandiri Bank Regional III Office Jakarta - Dita Novitayanti; Muhammad Doddy AB; Nursanita Nasution (Jurnal Ekonomi dan Perbankan Syariah, 2020)
This study aims to examine the effect of career development and motivation on employee performance. This research using quantitative research. Data were obtained by questionnaires to 37 respondents who worked at BSM Region III Office in 2020. The sampling technique in this study is non-probability sampling, with the Partial Least Square (PLS) approach is using a data analysis technique. Based on the results of data analysis,  career development has a significant effect on employee performance and motivation has a significant effect on employee performance. Therefore, by providing career development opportunities and motivation for employees will improve employee performance. Keywords: Career Development; Motivation; Employee Performance